2021
DOI: 10.51253/pafmj.v71i5.6089
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Body Measurements and Exercise With Blood Pressure Among Medical Students in Lahore

Abstract: Objective: To find out correlation of body measurements and exercise with blood pressure among medical students in Lahore, Pakistan. Study Design: Correlational study. Place and Duration of Study: Akhtar Saeed Medical and Dental College, Lahore, from May to Jul 2018. Methodology: A sample of 332 students was recruited through simple random sampling technique. Resting blood pressure in sitting position along with body mass index of respondents were taken after informed consent. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
1
Order By: Relevance
“…It is a considerable clinical marker in identifying the high risk adiposity phenotype 29 . In this study we were unable to find significant association of BP with BMI in adjusted model after controlling all the anthropometry indices however previous studies conducted on medical students in Pakistan reported significant association of BP with BMI 30,31 . According to the present study, abdominal fat deposition depicted by waist circumference is found to be a high-risk phenotype associated with hypertension after controlling other confounder variables.…”
Section: Discussioncontrasting
confidence: 89%
“…It is a considerable clinical marker in identifying the high risk adiposity phenotype 29 . In this study we were unable to find significant association of BP with BMI in adjusted model after controlling all the anthropometry indices however previous studies conducted on medical students in Pakistan reported significant association of BP with BMI 30,31 . According to the present study, abdominal fat deposition depicted by waist circumference is found to be a high-risk phenotype associated with hypertension after controlling other confounder variables.…”
Section: Discussioncontrasting
confidence: 89%
“…In Asia, Malaysia has the greatest e-cigarette prevalence (14%), followed by the Republic of Korea (7%), and China (0.05%). In 2018, the frequency of e-cigarette consumption was 7.1% in Pakistan, 0.02% in India, and 0.4% in Bangladesh [3].…”
Section: Editorialmentioning
confidence: 99%